The Validity and Reliability of The Instrument Assessment of Higher Order Thinking Skill on The Biological Scope Materials - Ganda Hijrah Selaras; Yuni Ahda; Heffi Alberida; Tri Putri Wahyuni (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2019)
High Order Thinking Skill (HOTS) requires students to connect, analyze, and also transform their knowledges and experiences. To determine students' high-level thinking skills, we can use assessment instruments. A good instrument should be valid and reliable so it is feasible to measure and assess what it wants to be measured and assessed. Therefore it is necessary to know the level of validity and reliability of the higher order thinking assessment instruments. The instrument used in this study in the scope of biology material. This type of research is descriptive research. The subjects of this study were students of grade X MIPA 5 SMA 5 Padang. Based on the results of data analysis, the assessment instrument of high order thinking skill on biological scope material is logically valid, empirical valid and reliable.